Influence of biomass burning on atmospheric aerosols over the western South China Sea: Insights from ions, carbonaceous fractions and stable carbon isotope ratios. (November 2018) - Song, Junwei; Zhao, Yan; Zhang, Yingyi; Fu, Pingqing; Zheng, Lishan; Yuan, Qi; Wang, Shan; Huang, Xiaofeng; Xu, Weihai; Cao, Zhixiang; Gromov, Sergey; Lai, Senchao
Abstract: Total suspended particle (TSP) samples were collected during a cruise campaign over the western South China Sea (SCS) from August to September 2014. Ten water-soluble ions (WSI), organic carbon (OC), elemental carbon (EC) and stable carbon isotope ratios of total carbon (δ 13 CTC ) were measured. The average concentrations of total WSI, OC and EC were 7.91 ± 3.44 μg/m 3, 2.04 ± 1.25 μg/m 3 and 0.30 ± 0.22 μg/m 3, respectively. Among the investigated WSI, sulfate (SO4 2− ), sodium (Na + ) and chloride (Cl − ) were the most abundant species, accounting for 39.2%, 24.5% and 14.3% of the total mass of the WSI, respectively. Significantly positive correlations of OC and EC with non-sea-salt potassium (nss-K + ), a tracer for biomass burning, suggest that biomass burning is the major source of carbonaceous aerosols. The values of δ 13 CTC ranged from −26.6‰ to −24.4‰ with an average of −25.3 ± 0.7‰. Based on the literature data of δ 13 CTC, back-trajectory analysis and satellite fire spots, we propose that C3 plant burning in Southeast Asia significantly contributes to carbonaceous aerosols over the western SCS. This is also supported by a good correlation between δ 13 CTC and the mass ratios of nss-K + /TC. Furthermore, high Cl − depletion (73 ± 23%) was observed in the aerosols over the western SCS. Given the neutralization of SO4 2− by ammonium (NH4 + ), excess nss-SO4 2- and oxalate (C2 O4 2− ) made major contributions to Cl − depletion in the samples strongly influenced by biomass burning. This study provides useful information to better understand the influence of biomass burning on atmospheric aerosols over the SCS. Graphical abstract: Image 1 Highlights: Ionic and carbonaceous fractions along with δ 13 C were measured in aerosols over the western SCS. Carbonaceous aerosols mainly originated from C3 plant burning. Biomass burning from the Indonesia islands had significant impact on aerosols over the SCS. High chloride depletion was observed in aerosols under the influence of biomass burning. Abstract : This study shows that biomass burning can strongly influence the concentrations and composition of aerosols over the SCS.